Síntese e caracterização de compósitos magnetoelétricos particulados de ferritas de Co e Ni e ferroelétricos no CFM - Zabotto, Fabio Luis (Universidade Federal de São Carlos, 2010)
Nowadays, the optimized magnetoelectric coupling in particulate composites is based on the optimization of the processing techniques, which support an integrity interface between the phases, and on the novel combinations of the ferroelectric and ferromagnetic phases. In this context, this work suggests the synthesis and characterization of particulate magnetoelectric composites of different ferroelectric systems, of compositions in the morphotropic phase boundary (MPB)- since they show a maximization of the piezoelectric coefficients- coupled with nickel or cobalt ferrites- since they show great magnetoestrictive coefficients. As ferroelectric phases, the lead zirconate titanate, or Pb(Zr0,53Tio,47)O3 (of simple perovskite structure), the lead titanate modified magneion niobate titanate, or 0,675Pb(Mg1/3Nb2/3)- 0,325PbTiO3 (of complex perovskite structure) and the lead barium niobate, or Pb0,61Ba0,39Nb2O6 (of tungsten bronze structure), where choosen. The ferroelectric/ferrite system composites were obtained in the molar ratio 80/20, by the conventional solid state and oxide mixing technique. The ceramic bodies were densified in different conditions, as a function of the time and temperature, by the conventional sintering process, or by the uniaxial hot pressing process. The relationship between the kind/combination of the phases, sintering techniques, and processing parameters, with the densification degree and the phases integrity was determined by structural, microestructural, physical and electrical characterization of the ceramic composites (with attention in those composed by nickel ferrite). As the main result, a processing protocol (validated only for the hot pressed composites, since the conventional sintering process generated conductive ceramics), independent of the constituent phases, which allows the synthesis adequate composites for research and application in the industry, were novelty determined. This protocol were also tested with significant results for composites based on cobalt ferrites. For all the cases of optimized processing conditions, dielectric, magnetic and magnetoelectric characterizations locking for the influences of the ferroelectric and/or magnetic phases in the multiferroic properties were performed. The values of magnetoelectric coefficients (xME) were close or higher than the most of the common particulate composites, and the PMN-PT/NFO shown the highest ratio dxME/dH of the studied materials. A general picture of the relationship between the magnetoelectric response and the research parameters, in this work, is presented, proving the relationship between the high density and integrity of the phases and the maximization of the magnetoelectric coupling.
Keywords: Magnetoelétrico; Prensagem uniaxial a quente; Piezoeletricidade; Magnetoestricção; CIENCIAS EXATAS E DA TERRA::FISICA